INFORMATION SYSTEMS USED IN IMMIGRATION CONTROL STRUCTURAL UNITS, ANALYSIS OF THEIR OPERATIONAL EFFECTIVENESS AND CAPABILITIES IN LATVIA - Bindemane, Sanita; Arbidāne, Iluta; Mietule, Iveta (Border Security and Management, 2018)
Research problem - during the implementation of various immigration control activities, the Immigration control structural units use the range of information systems that need to be improved. The aim of the research is to explore the information systems used in Immigration control structural units, their operational efficiency and capabilities as well as bring forward several suggestions in order to improve the use of information systems. Research tasks: 1) to analyse regulations related to information systems, their classification and legal framework; 2) to analyse the competence of using information systems in Immigration control structural units; 3) to explore the possibilities of using the information systems in Immigration control structural units for the purposes of planning duties; 4) to carry out SWOT analysis and make comparison of mobile information systems. Research methods: analysis of documents, monographic, logical – constructive, questionnaire, SWOT analysis. During the research, the legal and practical aspects in the use of information systems were clarified. Based on the aim and tasks set out for the research, the authors brings forward several possible solutions and suggestions on ways how to improve the information systems used by Immigration control structural units.